Prognostic value of clinical and immunological markers in acute phase of SFTS virus infection. (15th May 2014) - Ding, Y.‐P.; Liang, M.‐F.; Ye, J.‐b.; Liu, Q.‐h.; Xiong, C.‐h.; Long, B.; Lin, W.‐b.; Cui, N.; Zou, Z.‐q.; Song, Y.‐l.; Zhang, Q.‐f.; Zhang, S.; et al.
Abstract SFTS virus (SFTSV) is a novel bunyavirus that causes severe fever with thrombocytopenia syndrome (SFTS), an emerging infectious disease that occurred in China in recent years, with an average case fatality rate of 10–12%. Intervention in the early clinical stage is the most effective measure to reduce the mortality rate of disease. To elucidate the natural course of and immune mechanisms associated with the pathogenesis of SFTSV, 59 laboratory‐confirmed SFTS patients in the acute phase, who were hospitalized between October 2010 and September 2011, were enrolled in this study, and the patients sera were dynamically collected and tested for SFTSV viral RNA load, 34 cytokines or chemokines and other related laboratory parameters. All clinical diagnostic factors in the acute phase of SFTS were evaluated and assessed. The study showed that the severity of the disease in 11 (18.6%) patients was associated with abdominal pain (p 0.007; OR = 21.95; 95% CI, 2.32–208.11) and gingival bleeding (p 0.001; OR = 122.11; 95% CI, 6.41–2328). The IP‐10, TNF‐α, IL‐6, IL‐10, granzyme B and HSP70 levels were higher over the 7–8 days in severe cases, accompanied by altered AST, CK and LDH levels. HSP70 (p 0.012; OR = 8.29; 95% CI, 1.58–43.40) was independently correlated with the severity of the early acute phase of SFTSV infection. The severity of SFTS can be predicted based on the presence of symptoms such as abdominal pain and gingival bleeding and on the level of HSP70 in the acute phase of the disease.